2018
DOI: 10.1177/2158244017745577
|View full text |Cite
|
Sign up to set email alerts
|

Intersex Studies: A Systematic Review of International Health Literature

Abstract: There is a need to better understand contemporary issues of nomenclature and group construction around people with intersex variations shaping health research and practices-including their framing within concepts like disorders of sex development (DSD), intersex, or the lesbian, gay, bisexual, transgender, and intersex (LGBTI) umbrella. This article reviews health literature in the broad field of Intersex Studies since 2015. It outlines the contexts, theoretical lenses, methods and participant numbers, framing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 63 publications
2
48
0
2
Order By: Relevance
“…Moreover, differences in lifestyle factors that are associated with sex and gender, such as diet, physical activity, tobacco use and alcohol consumption, also correlate with the epidemiology of diseases [9][10][11] . Nonetheless, there are still open questions regarding health differences across the gender spectrum, reflected by the scarcity of studies dedicated to intersex, transgender and nonbinary individuals 12,13 . Initiatives, such as the Global Trans Research Evidence Map 14 , foster research access in this area to improve our understanding of the effects of medical interventions on health and life quality across the gender spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, differences in lifestyle factors that are associated with sex and gender, such as diet, physical activity, tobacco use and alcohol consumption, also correlate with the epidemiology of diseases [9][10][11] . Nonetheless, there are still open questions regarding health differences across the gender spectrum, reflected by the scarcity of studies dedicated to intersex, transgender and nonbinary individuals 12,13 . Initiatives, such as the Global Trans Research Evidence Map 14 , foster research access in this area to improve our understanding of the effects of medical interventions on health and life quality across the gender spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Following extensive advocacy by intersex people, several countries, international bodies, and American medical groups, including Human Rights Watch, the World Health Organization, and Amnesty International, have recommended delaying surgeries so that intersex people themselves can make informed decisions about what is best for them [ 7 , 9 – 13 ]. Alongside this, a new community-centered research literature is beginning to emerge, highlighting intersex voices and experiences [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, intersex people narrated their experience to challenge medical practices (Chase, ; Dreger, ), some experts called for a moratorium on medical intervention (Diamond & Sigmundson, ), a case study long used to justify intervention was exposed for abusive treatment and scientific fraud (Colapinto, ), and a novel with an intersex protagonist received widespread critical acclaim (Eugenides, ). Qualitative social research has since often confirmed that people with intersex characteristics frequently experience stigma, often in medical encounters that are ostensibly aimed at supporting their well‐being (see e.g., Alderson, Madill, & Balen, ; Boyle, Smith, & Liao, ; Davis, ; Endberg, Möller, Hagenfeldt, Nordenskjöld, & Frisén, ; Meyer‐Bahlburg, Khuri, Reyes‐Portillo, & New, ; Preves, , see Jones, , for a recent review).…”
Section: Introductionmentioning
confidence: 99%
“…anecdotal healthcare information on YouTube often contradicts information put forward by medical professionals (Madathil et al, ). YouTube videos with personal narratives are preferred over those that foreground public health information alone (Yiannakoulias et al, ), and autobiographical research remains the most common form of social science evidence in intersex studies (Jones, ). In recent years, a greater number of personal narrative videos pertaining to people with intersex characteristics have appeared online (see The Interface Project, n.d., in addition to those described below).…”
Section: Introductionmentioning
confidence: 99%